KOMITMEN ORGANISASIONAL MEMEDIASI IKLIM ORGANISASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KEPUASAN KERJA (Studi Kasus Guru SD Negeri di Kecamatan Plantungan) - 11.52.02.0142, Sulistyantini (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study to the purpose of thisnstudy is analyze the effect of organizational climate and leadership mediated by Organizational Commitment. The population is made ââan object of primary school teachers in the district civil servants Plantungan Kendal totaling 100 people. Sampling was purposive sampling methods that selected according to criteria that are determined to be the respondent. The purposive sampling results can be seen that the number of samples in this study were 100 respondents. The results prove that the models ability to explain the influence of climate variables and the Organization of the Principal Leadership Organizational commitment .The Influence of Organizational Climate, Principal Leadership, Organizational Commitment to Teacher Job Satisfaction. Mediation Organizational Climate with Organizational Commitment has a positive and significant impact on Job Satisfaction Elementary School Teachers in District Plantungan Kendal. Principal leadership by mediating Organizational Commitment has a positive and significant effect on Job Satisfaction Elementary School Teachers in District Plantungan Kendal. Key Words: Organizational Climate, Principal Leadership, Organizational Commitment, Job Satisfaction